The impact of digital technologies on the facilitation of internationalization strategies of the SMEs: The case of Born-Digital companies - KARIM, SYED FAZAL (My University, 2024)
With the growing prominence of digitalization and the push for globalization, there is increas-ing research on how the transformation and adoption of technology have changed the entry of companies and if it has made it easier or harder. The impact and benefits of technology achieved through being born digital are said to be found in the literature to provide the com-panies with unique skills and capabilities that help these small but innovative companies counter and challenge traditional players in the market. This study examines the unique role and impact of born-digital enterprises in navigating glob-al marketplaces and entering new markets, considering the increasing globalization and digital revolution. The research utilizes a mixed-method approach, combining surveys and interviews with professionals from six successful born-digital organizations to provide the answers. It analyzes the inherent advantages of these entities, such as innovation, agile decision-making, and customer-centric operations, which enable their worldwide development, and the find-ings further highlight the inherent ability of digital natives to effectively use information and technology to make strategic decisions and respond to market changes, in contrast to the de-layed adoption of digital requirements by traditional enterprises. It also highlights the crucial role of these born-digital organizations in transforming global commerce and emphasizes a shift in the way established companies need to adapt in order to stay competitive; it fills a significant knowledge vacuum by examining how digitalization drives internationalization and transforms it, too. It provides actual evidence and validates existing theoretical frameworks in the literature, as well as highlights areas where further research is required.

With the growing prominence of digitalization and the push for globalization, there is increasing research on how the transformation and adoption of technology have changed the entry of companies and if it has made it easier or harder. The impact and benefits of technology achieved through being born digital are said to be found in the literature to provide the companies with unique skills and capabilities that help these small but innovative companies counter and challenge traditional players in the market. This study examines the unique role and impact of born-digital enterprises in navigating global marketplaces and entering new markets, considering the increasing globalization and digital revolution. The research utilizes a mixed-method approach, combining surveys and interviews with professionals from six successful born-digital organizations to provide the answers. It analyzes the inherent advantages of these entities, such as innovation, agile decision-making, and customer-centric operations, which enable their worldwide development, and the findings further highlight the intrinsic ability of digital natives to effectively use information and technology to make strategic decisions and respond to market changes, in contrast to the delayed adoption of digital requirements by traditional enterprises. It also highlights the crucial role of these born-digital organizations in transforming global commerce and emphasizes a shift in the way established companies need to adapt in order to stay competitive; it fills a significant knowledge vacuum by examining how digitalization drives internationalization and transforms it, too. It provides actual evidence and validates existing theoretical frameworks in the literature, as well as highlights areas where further research is required.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|; fi=Kansainvälisen liiketoiminnan kandidaattiohjelma|en=Bachelor Programme in International Business|